The role of extracellular vesicles in malaria biology and pathogenesis - Natalia Guimaraes Sampaio; Lesley Cheng; Emily M. Eriksson (Malaria Journal, 2017)
Abstract In the past decade, research on the functions of extracellular vesicles in malaria has expanded dramatically. Investigations into the various vesicle types, from both host and parasite origin, has revealed important roles for extracellular vesicles in disease pathogenesis and susceptibility, as well as cell–cell communication and immune responses. Here, work relating to extracellular vesicles in malaria is reviewed, and the areas that remain unknown and require further investigations are highlighted.